Italian syntax and universal grammar - Cinque, Guglielmo 1948- (Cambridge Univ. Press, 1995)
Guglielmo Cinque is one of the world's leading theoretical syntacticians, and is particularly known for his application of recent theory to the analysis of Italian. This volume brings together ten of Professor Cinque's essays, some of which are published here for the first time, and some of which have not hitherto been easily available. They explore a wide range of aspects of Italian syntax, including the grammar of relative and "pseudo-relative" clauses in the complement of perception verbs, impersonal si constructions, and the position and argument structure of adjectives in the noun phrase. The volume considers the implications of Cinque's work on Italian syntax for generative grammar more broadly, and comparers Italian with the syntax of other Romance and also Germanic languages. It will be welcomed by all those working on Italian syntax, and on theoretical syntax more generally.
Keywords: Italiaans; Syntaxis; Italienisch; Syntax; Italian language -- Syntax; Wahrnehmung; Subjektloser Satz; Relativsatz; Nominalsatz; Verb; Universalgrammatik; Aufsatzsammlung